2021
DOI: 10.1021/acsomega.1c03951
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Synthesis of Fe–BTC–PEG Metal–Organic Complex: An Effective and Safety Nanocarrier for Anticancer Drug Delivery

Abstract: The porous metal–organic complexes are emerging as novel carriers for effective and safe delivery of drugs for cancer treatment, minimizing the side effect of drug overuse during cancer treatment. This study fabricated the Fe–BTC–PEG metal–organic complex from Fe ions, trimesic acid, and poly(ethylene glycol) as precursors using an ultrasonic-assisted method. The morphology and crystallinity of the resultant complex were observed by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…PEG is an FDA-approved, hydrophilic, and flexible polymer that has been proven to be safe for use in biomedical applications [ 150 ]. PEG has been used to deliver chemotherapeutics [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ], anti-inflammatory drugs [ 160 ], antibiotics [ 161 , 162 ], and bisphosphonates [ 163 ]. Additionally, vitamins [ 164 ], phenols [ 165 ], and hormones [ 166 ] have been delivered using PEG.…”
Section: Synthetic Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%
“…PEG is an FDA-approved, hydrophilic, and flexible polymer that has been proven to be safe for use in biomedical applications [ 150 ]. PEG has been used to deliver chemotherapeutics [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ], anti-inflammatory drugs [ 160 ], antibiotics [ 161 , 162 ], and bisphosphonates [ 163 ]. Additionally, vitamins [ 164 ], phenols [ 165 ], and hormones [ 166 ] have been delivered using PEG.…”
Section: Synthetic Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%
“…[26] We have recently found the preparation of a complex FeÀ BTC/PEG by ultrasonic-assisted method. [27] As our contribution, we explored the direct synthesis of FeÀ BTC from the precursors iron nitrate and trimesic acid in water under ultrasonic irradiation, employing two protocols, procedures (1) and ( 2), each performed using different ultrasonic setups and procedures.…”
Section: Introductionmentioning
confidence: 99%
“…As described, various MOF structures have been prepared by sonochemical technique over the last years, however, the ultrasonic method has been poorly explored for the Fe−BTC preparation [26] . We have recently found the preparation of a complex Fe−BTC/PEG by ultrasonic‐assisted method [27] …”
Section: Introductionmentioning
confidence: 99%
“…This high 5-FU loading of Fe-BDC-PEG is comparable with that of the Fe-BTC-PEG complex and reasonable for drug-delivery purpose. 36,47 One of the main properties of advanced materials that is effectively used for drug delivery is slow release on purpose. For the drug-release test, the loaded material was immersed in different pH solutions of phosphate-buffered saline PBS (pH 7.4, 6.8, and 5), and 5-FU concentration was determined by UV−vis spectrometry at a wavelength of λ max = 266 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was demonstrated that DOX@bioMOC-Zn­(Cys) in nanoscale size accelerated the anticancer drug uptake via the endo/lysosomal pathway. In our previous work, we successfully incorporated ferric ions, trimesic acid, and poly­(ethylene glycol) to produce a porous Fe-BTC-PEG MOC . The prepared MOC had a maximum loading capacity of 364 mg/g for the 5-FU drug.…”
Section: Introductionmentioning
confidence: 99%